Artificial Intelligence, Transhumanism and the Digital Spirit: Ethical Challenges in the Abrahamic Traditions - Rizky HK, Muhammad (Universitas Islam Negeri Raden Intan Lampung, 2026)
Abrahamic religions confront new theological and ethical issues as artificial intelligence (AI) increasingly mediates moral judgments and reconfigures human identity. This article explores the ethical, anthropological, and spiritual implications of AI and transhumanism using a comparative hermeneutic analysis based on Islam, Christianity, and Judaism. Using recent peer-reviewed literature and the writings of Yuval Noah Harari, Paul Ricœur, Karen Armstrong, and Nidhal Guessoum, the study presents AI as a symbolic